2007
DOI: 10.1111/j.1651-2227.2007.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver disease as risk factor for cystic fibrosis‐related diabetes development

Abstract: Severe liver disease was found to significantly increase the risk of developing cystic fibrosis-related diabetes. Patients with liver disease should be scheduled for earlier diabetes screening in order to identify and possibly treat glucose intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 29 publications
5
27
0
1
Order By: Relevance
“…Female sex has been noted to be a significant risk factor for diabetes in CF, and we saw evidence of this association in this study, although significance was not achieved, which may be due to insufficient power (13). Other associated CF complications such as lung transplantation (32), markers of chronic inflammation (24), and liver disease (33) were not evaluated.…”
Section: Discussionmentioning
confidence: 48%
“…Female sex has been noted to be a significant risk factor for diabetes in CF, and we saw evidence of this association in this study, although significance was not achieved, which may be due to insufficient power (13). Other associated CF complications such as lung transplantation (32), markers of chronic inflammation (24), and liver disease (33) were not evaluated.…”
Section: Discussionmentioning
confidence: 48%
“…CF liver disease predisposes patients to glucose abnormalities and diabetes (55,56). However, it remains unclear whether neonatal liver pathologies in CF influence glucose and insulin regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition associated with portal hypertension is likely multifactorial with decreased nutrient absorption, increased resting energy expenditure, anorexia and decreased caloric intake. There may be a link between CFLD and increased insulin resistance leading to a higher incidence of CF related diabetes [30]. A single center retrospective case–control study showed an odds ratio of 4.8 (95% CI, 2.49, 9.17) for CF related diabetes in those with cirrhosis and portal hypertension, using a surrogate marker (thrombocytopenia) for cirrhosis with portal hypertension [31].…”
Section: Cystic Fibrosis Related Cirrhosis With and Without Portalmentioning
confidence: 99%